Melatonin and ethanol intake exert opposite effects on circulating estradiol and progesterone and differentially regulate sex steroid receptors in the ovaries, oviducts, and uteri of adult rats - Chuffa, Luiz Gustavo A. [UNESP]; Seiva, Fábio R.F. [UNESP]; Fávaro, Wagner José [UNESP]; Amorim, João Paulo A. [UNESP]; Teixeira, Giovana R. [UNESP]; Mendes, Leonardo O. [UNESP]; Fioruci-Fontanelli, Beatriz A. [UNESP]; Pinheiro, Patricia Fernanda F. [UNESP]; Martinez, Marcelo; Martinez, Francisco Eduardo [UNESP] (Elsevier, 2013)
Chronic ethanol intake is associated with sex hormone disturbances, and it is well known that melatonin plays a key role in regulating several reproductive processes. We report the effects of ethanol intake and melatonin treatment (at doses of 100. μg/100. g. BW/day) on sex hormones and steroid receptors in the ovaries, oviducts and uteri of ethanol-preferring rats. After 150 days of treatment, animals were euthanized, and tissue samples were harvested to evaluate androgen, estrogen, progesterone and melatonin receptor subunits (AR, ER-α and ER-β, PRA, PRB and MT1R, respectively). Melatonin decreased estradiol (E2) and increased progesterone (P4) and 6-sulfatoxymelatonin (6-STM), while an ethanol-melatonin combination reduced both P4 and E2. Ovarian AR was not influenced by either treatment, and oviduct AR was reduced after ethanol-melatonin combination. Oviduct ER-α, ER-β and uterine ER-β were down-regulated by either ethanol or melatonin. Conversely, ovarian PRA and PRB were positively regulated by ethanol and ethanol-melatonin combination, whereas PRA was down-regulated in the uterus and oviduct after ethanol consumption. MT1R was increased in ovaries and uteri of melatonin-treated rats. Ethanol and melatonin exert opposite effects on E2 and P4, and they differentially regulate the expression of sex steroid receptors in female reproductive tissues. © 2013 Elsevier Inc.
Keywords: Ethanol; Female reproductive tissue; Melatonin; Sex hormone; Sex steroid receptor; 6 hydroxymelatonin o sulfate; alcohol; androgen receptor; beta actin; daidzein; estradiol; estrogen receptor alpha; estrogen receptor beta; genistein; melatonin; melatonin 1 receptor; progesterone; progesterone receptor A; progesterone receptor B; alcohol consumption; alcoholism; animal experiment; animal tissue; controlled study; dietary intake; enzyme activity; enzyme regulation; female; nonhuman; nutritional assessment; ovary; oviduct; protein expression; protein function; rat; uterus